Flight tone characterisation of the South American malaria vector Anopheles darlingi (Diptera: Culicidae) - Montoya, Jose Pablo (Mem Inst Oswaldo Cruz, 2021)
BACKGROUND: Flight tones play important roles in mosquito reproduction. Several mosquito species utilise flight tones for mate localisation and attraction. Typically, the female wingbeat frequency (WBF) is lower than males, and stereotypic acoustic behaviors are instrumental for successful copulation. Mosquito WBFs are usually an important species characteristic, with female flight tones used as male attractants in surveillance traps for species identification. Anopheles darlingi is an important Latin American malaria vector, but we know little about its mating behaviors. OBJECTIVES: We characterised An. darlingi WBFs and examined male acoustic responses to immobilised females. METHODS: Tethered and free flying male and female An. darlingi were recorded individually to determine their WBF distributions. Male-female acoustic interactions were analysed using tethered females and free flying males. FINDINGS: Contrary to most mosquito species, An. darlingi females are smaller than males. However, the male’s WBF is ~1.5 times higher than the females, a common ratio in species with larger females. When in proximity to a female, males displayed rapid frequency modulations that decreased upon genitalia engagement. Tethered females also modulated their frequency upon male approach, being distinct if the interaction ended in copulation or only contact. MAIN CONCLUSIONS: This is the first report of An. darlingi flight acoustics, showing that its precopulatory acoustics are similar to other mosquitoes despite the uncommon male:female size ratio, suggesting that WBF ratios are common communication strategies rather than a physical constraint imposed by size.